A15 MICROBES MEDIATE FIBER-INDUCED INFLAMMATION IN IBD. (26th February 2020) - Armstrong, H; Dickner, R; Rieger, A; Mander, I K; Jerasi, J; Santer, D; Valcheva, R; Dijk, S I; Petrova, A; Dieleman, L A; Carroll, M W; Huynh, H Q; et al.
Abstract: Background: The etiology of inflammatory bowel diseases (IBD ) remains unknown, although gut microorganisms and diet have been implicated. Dietary fibers pass through the bowel undigested and are fermented within the intestine by microbes, promoting gut health. However, many IBD patients describe experiencing sensitivity to fibres. Interestingly, fiber receptors on immune cells are able to interact with fibers typically found on the surface of fungal cells (which share properties with dietary fibers), for example, resulting in a paradoxical pro-inflammatory response. Aims: As an altered microbial composition is a hallmark of IBD, we hypothesized that the loss of fiber fermenting-microbes populating the IBD gut could lead to dietary fibers not being efficiently broken down into their beneficial biproducts, resulting in binding of intact fibers to pro-inflammatory host cell receptors. This can ultimately drive pro-inflammatory responses and a microenvironment that promotes continued dysbiosis and increased pathogenicity of select microbes, as observed in IBD. Methods: Fiber receptor expression gut was examined using immunohistochemistry and flow cytometry and demonstrated elevated receptor expression due to increased presence of immune cells in IBD patient biopsies. Cytokine secretion, in response to fiber (5mg/mL) or pre-fermented fibers, cultured with microbes of interest, was measured by ELISAs in cell lines in vitro and biopsy tissues cultured ex vivo . Results: Whole-fibers induced pro-inflammatory cytokine production in macrophage, monocytes, and neutrophils. Specific microbes were capable of fermenting fiber, measured by gas chromatography. Pre-fermentation of fibers by these microbes reduced inflammatory cytokine production. The fiber oligofructose increased IL-1β in pediatric CD (n=44) and UC (n=29) biopsies cultured ex vivo but not in non-IBD (n=25). The increase was greater in patients with more severe disease. Pre-fermentation of oligofructose by bacteria reduced this secretion of IL-1β. Whole-microbe intestinal washes from severe IBD patients were unable to ferment oligofructose or reduce fiber-associated inflammation in macrophage cells compared to remission or non-IBD children. Statistical analysis of food frequency questionnaire (FFQ) data on fiber consumption demonstrated that fiber-associated inflammation in patient biopsies cultured ex vivo (ELISA and qPCR) correlated with fiber avoidance (FFQ). Conclusions: Comparing in vitro findings to our patient FFQs, intestinal washes (microbe abundance), and detailed patient history will better define the relationship between microbes, dietary fibers, and gut inflammation in IBD. This will allow for tailored dietary intervention through dietary recommendations, prebiotic, and/or probiotic therapies. Funding Agencies: CCCWeston Foundation, WCHRI